Natural variability masks climate change sea surface temperature signals: a comparison between the Baltic Sea, North Sea and North Atlantic Ocean - H. Mashayekh Poul; M. Gröger; S. Karsten; B. Mayer; T. Pohlmann; H. E. M. Meier (Climate Dynamics, 2025)
Climate variability in marine environments, particularly sea surface temperature (SST), is influenced by natural fluctuations occurring at various temporal and spatial scales. Distinguishing between anthropogenic climate change trends and natural variability is crucial for understanding the complex dynamics of ocean temperatures. This study applies the concept of Time of Emergence (ToE) to estimate when the signal of long-term climate change becomes distinguishable from natural variability in SST for different seasons. The study focuses on the North Sea, Baltic Sea, and North Atlantic Ocean, utilizing 30 ensemble members of simulation from a regional climate model system, MPIOM-REMO, with slightly different initial conditions. The results reveal that winter ToEs emerge earlier than summer ToEs in all study areas, mainly driven by larger winter SST changes and show that shallow coastal seas like the North and Baltic Seas experience earlier ToEs than the deep central North Atlantic. These findings emphasize the influence of regional processes, such as sea ice dynamics and changes in stratification, on the spatial and temporal variability of ToE patterns.

Impact of ocean data assimilation on climate predictions with ICON-ESM - Holger Pohlmann; Sebastian Brune; Kristina Fröhlich; Johann H. Jungclaus; Christine Sgoff; Johanna Baehr (Climate Dynamics, 2023)
We develop a data assimilation scheme with the Icosahedral Non-hydrostatic Earth System Model (ICON-ESM) for operational decadal and seasonal climate predictions at the German weather service. For this purpose, we implement an Ensemble Kalman Filter to the ocean component as a first step towards a weakly coupled data assimilation. We performed an assimilation experiment over the period 1960–2014. This ocean-only assimilation experiment serves to initialize 10-year long retrospective predictions (hindcasts) started each year on 1 November. On multi-annual time scales, we find predictability of sea surface temperature and salinity as well as oceanic heat and salt contents especially in the North Atlantic. The mean Atlantic Meridional Overturning Circulation is realistic and the variability is stable during the assimilation. On seasonal time scales, we find high predictive skill in the tropics with highest values in variables related to the El Niño/Southern Oscillation phenomenon. In the Arctic, the hindcasts correctly represent the decreasing sea ice trend in winter and, to a lesser degree, also in summer, although sea ice concentration is generally much too low in both hemispheres in summer. However, compared to other prediction systems, prediction skill is relatively low in regions apart from the tropical Pacific due to the missing atmospheric assimilation. Further improvements of the simulated mean state of ICON-ESM, e.g. through fine-tuning of the sea ice and the oceanic circulation in the Southern Ocean, are expected to improve the predictive skill. In general, we demonstrate that our data assimilation method is successfully initializing the oceanic component of the climate system.

The prediction of surface temperature in the new seasonal prediction system based on the MPI-ESM coupled climate model - J. Baehr; K. Fröhlich; M. Botzet; D. I. V. Domeisen; L. Kornblueh; D. Notz; R. Piontek; H. Pohlmann; S. Tietsche; W. A. Müller (Climate Dynamics, 2015)

An assessment of a multi-model ensemble of decadal climate predictions - A. Bellucci; R. Haarsma; S. Gualdi; P. J. Athanasiadis; M. Caian; C. Cassou; E. Fernandez; A. Germe; J. Jungclaus; J. Kröger; D. Matei; W. Müller; et al. (Climate Dynamics, 2015)

Combined analysis of field and model data: A case study of the phosphate dynamics in the German Bight in summer 1994 - Th. Pohlmann; Th. Raabe; R. Doerffer; S. Beddig; U. Brockmann; S. Dick; M. Engel; K. -J. Hesse; P. König; B. Mayer; A. Moll; D. Murphy; et al. (Ocean Dynamics, 1999)

Mesoscale structures, fluxes and water mass variability in the German Bight as exemplified in the KUSTOS- experiments and numerical models - G. A. Becker; H. Giese; K. Isert; P. König; H. Langenberg; Th. Pohlmann; C. Schrum (Ocean Dynamics, 1999)

The atmospheric impact on fluxes of nitrogen, POPs and energy in the German Bight - M. Schulz; J. Beusekom; K. Bigalke; U. Brockmann; W. Dannecker; H. Gerwig; H. Grassl; C. -J. Lenz; K. Michaelsen; U. Niemeier; T. Nitz; E. Plate; et al. (Ocean Dynamics, 1999)

Exchange of matter and energy between the Wadden Sea and the coastal waters of the German Bight-Estimations based on numerical simulations and field measurements - S. Dick; U. H. Brockmann; J. E. E Beusekom; B. Fabiszisky; M. George; U. Hentschke; K. -J. Hesse; B. Mayer; Th. Nitz; Th. Pohlmann; K. Poremba; K. Schaumann; et al. (Ocean Dynamics, 1999)